The additive effect of biochar amendment and simulated nitrogen deposition stimulates the plant height, photosynthesis and accumulation of NPK in pecan (Carya illinoinensis) seedlings. Issue 4 (26th July 2020) - Hou, Zhiying; Tang, Yiquan; Li, Caiyun; Lim, Kean-Jin; Wang, Zhengjia
Abstract: This work investigated the effective doses of biochar (BC) amendment with simulated nitrogen deposition on the stimulation of pecan ( Carya illinoinensis ) growth. A total of nine conditions combining three levels of BC—BC0, 0 t ha −1 year −1 ; BC20, 20 t ha −1 year −1 ; and BC40, 40 t ha −1 year −1 —and three levels of simulated nitrogen deposition—N0, 0 kg N ha −1 year −1 ; N50, 50 kg N ha −1 year −1 ; and N150, 150 kg N ha −1 year −1 —were applied throughout 1 year on the pecan-grafted seedlings of cultivar 'Pawnee'. The growth, photosynthesis, chlorophyll and nutrient content in the seedlings were measured. The soil bulk density, pH, nitrogen content and enzymatic activities were also measured. Biochar amendment reduced soil bulk density and elevated soil pH. Meanwhile, aided by BC amendment, the inorganic nitrogen content and enzyme activities increased with increasing doses of nitrogen. In the absence of BC amendment, the seedlings' height, photosynthesis and chlorophyll pigments were only stimulated by a low level of simulated nitrogen deposition (N50), whereas a high level of simulated nitrogen deposition (N150) impeded the growth. The seedlings improved the most under the combined treatment of BC20N150, wherein the seedling heights, photosynthesis and total chlorophyll improved by 22 %, 70 % and 40 %, respectively, compared to those treated solely with BC20. Further increase of nitrogen retention in the soil by the BC40 did not further improve the growth of the seedlings, suggesting the possible mechanisms involve nutrient uptake and usage dynamic in the seedlings. The BC amendment alleviated the antagonist effect from simulated nitrogen deposition that suppressed the absorption of phosphorus, potassium and iron. The effect of applying both BC amendment and simulated nitrogen deposition to the growth of seedlings was additive at fertilizing tree species. Abstract : This work investigated the effect of combining biochar (BC) amendment and simulated nitrogen deposition on the growth of pecan seedlings at varying doses. Under the combined treatment of a low level of BC amendment and a high level of stimulated nitrogen deposition, the seedlings' height, photosynthetic ability and total chlorophyll content improved the most compared with BC treatment alone. The BC amendment alleviated the antagonist effect from simulated nitrogen deposition that suppressed the absorption of phosphorus, potassium and iron. The effect of applying both BC amendment and simulated nitrogen deposition to the growth of seedlings was additive at fertilizing tree species.